2021
DOI: 10.31295/ijhms.v4n1.440
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education with android-based application media to increase knowledge, attitudes, and behaviors of pregnant women about chronic energy deficiency (KEK)

Abstract: Pregnant women are a very vulnerable group to nutritional problems. The lack of knowledge, attitude, and behavior towards nutrition is the main cause of KEK (chronic energy deficiency) in pregnant women. The purpose of this study was to design an android-based application based on a needs analysis to improve nutritional knowledge and attitudes of pregnant women about KEK. The research method was qualitative research, while the design used a combined method between Research and Development (R&D) and Pre-Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…The results of the present study were in accordance to the findings of Preston et al [5] reported that patients with stage 3 to 4 CKD had increased CIMT compared with normotensive volunteers. Lu Xia Zhang et al [6] in their study on stage 2-3 CKD patients (i.e., mild and moderate renal insufficiency), found significantly increased CIMT in these patients and concluded that arterial change might occur in the course of CKD earlier than previously believed.This compares favorably with findings by Zoungas et al [7] who found significantly thickened CIMT in CKD patients compared with controls (0.89 ± -0.17 vs 0.73 ± -0.13 mm, respectively). Some other authors also reported similar findings [8,9] .…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study were in accordance to the findings of Preston et al [5] reported that patients with stage 3 to 4 CKD had increased CIMT compared with normotensive volunteers. Lu Xia Zhang et al [6] in their study on stage 2-3 CKD patients (i.e., mild and moderate renal insufficiency), found significantly increased CIMT in these patients and concluded that arterial change might occur in the course of CKD earlier than previously believed.This compares favorably with findings by Zoungas et al [7] who found significantly thickened CIMT in CKD patients compared with controls (0.89 ± -0.17 vs 0.73 ± -0.13 mm, respectively). Some other authors also reported similar findings [8,9] .…”
Section: Discussionsupporting
confidence: 87%
“…Through a significant value <0.05, then according to the decision-making criteria, H0 is rejected. That is, there is a difference in changes in knowledge, attitudes, and behavior/actions towards reproductive health education with multimedia video learning towards improving the behavior of preventing pathological fluor albus (leucorrhoea) in adolescent girls (Ananda et al, 2022;Lestari et al, 2021). Furthermore, to find out the difference between each variable individually, it can be seen in the Between-Subjects Effects table.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study, Bellon et al (2019), compared the results of the so-called Hamburg modification of Frey's operation; as a result, the advantages of such an operation over other duodenalpreserving resections of the pancreatic head were revealed; exo-, endocrine function of a pancreas did not differ from the point of view of control of a pain syndrome and the life quality (Konstantinidis et al, 2010). At the same time, the authors pointed out two important findings, namely: continued alcohol intake after surgery was significantly associated with relapse of pain; there was no reliable data on the duration of chronic pancreatitis, it was noted that almost all patients had terminal disease stage (Bellon et al, 2019;Yarmukhamedova et al, 2021;Lestari et al, 2021;Widana et al, 2020). In 2012, Dutch researchers have concluded that although the choice of the surgery based on pathological anatomical changes allows obtaining results of pain control in chronic pancreatitis from excellent to satisfactory ones, however, an early Surgery intervention performed before many endoscopic treatment attempts and the need for strong analgesics may (Wilcox et al, 2014), where no reliable relationship was found between the findings and the presence and severity of pain by comparing the surveys of patients and their imaging data.…”
Section: Methodsmentioning
confidence: 99%